The effect of different combinations of physical activity and natural environment videos on children's attention levels between class breaks - Xiao Luo; Meng Tao; Jiahao Lu; Li Lu; Xiaolong He (BMC, 2023)
Abstract Background Physical activity intervention and watching natural environment videos have been proven to improve young children's attention levels. However, evidence comparing the improvement effects of different combinations of the two activities has rarely been reported. By comparing the differences in the improvement effects of four combinations of physical activities and watching natural environment videos on young children's attention levels, this study can enrich the evidence in this research field and also provide a reference for arranging effective intervention methods for children's attention recovery between classes. Method A total of 152 children aged 4 to 6 years were recruited and randomly divided into four intervention groups: (1) physical activity intervention first and thereafter watching a natural environment video group (activity + video group), (2) watching a natural environment video first and thereafter the physical activity intervention group (video + activity group), (3) physical activity-based group, and (4) natural environment video-based group. Physical activity involved 4 min of moderate-intensity basic physical fitness combination training. The subjects wore the Pico Neo pioneer version of the VR glasses all-in-one machine to watch a natural environment video. Thereafter, population sociological variables and daily physical activity levels were investigated. Auditory and visual sustained attention tests were performed before and after intervention in each group. Result The auditory attention post-test scores of the four groups showed an improvement trend compared with the pretest scores. In particular, the activity + video group (F = 10.828; ɳp2 = 0.226; p = 0.002) and natural environment video-based group (F = 9.452; ɳp2 = 0.203; p = 0.004) have the best improvement effect. For visual attention, only the activity + video group showed a significant improvement trend (F = 4.287; ɳp2 = 0.104; p = 0.045), while the other three groups showed a downward trend in scores. Conclusions Among the different intervention combinations, the physical activity intervention first and watching natural environment videos thereafter group has the best effect on improving children's attention during recess. Physical activity interventions at the end of recess adversely affect young children's visual attention levels at the beginning of the class. Therefore, this study recommends that children should not engage in physical activity interventions in the second half of the class break. Lastly, the current research recommends presenting the content of physical activity interventions first and further improving their attention thereafter by watching natural environment videos.